Temperatura, luz e tolerância à dessecção na germinação de sementes de açaí-do-Amazonas - Costa, Carla Rafaele Xavier [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Euterpe precatoria Mart. Is a widely distributed palm tree in the Amazon basin. The seed constitutes one of the main mechanisms of propagation of this palm tree, because has no tillers. Several factors can influence the germination of seeds, such as temperature, light and water content in seeds. The aim of this study was to investigate the influence of different temperatures, light regimes and desiccation tolerance in the germination of Euterpe precatoria Mart. seeds. In the study of light and temperature, the experimental design was randomized; the treatments were arranged in a factorial 6 x 2 (six conditions of temperature; 20 °C, 25 °C, 30 °C, 35 °C, 20-30 °C and 25-35 °C, and two conditions of light: lightness and darkness) with four replications, and each plot was composed of 25 seeds. In the assay of tolerance to desiccation, the experimental design was completely randomized; the treatments were five seeds moisture (27%, 20 %, 13%, 12% and 11%); were four replications, each plot was composed of 25 seeds. The number of seeds with the appearance of the button seedling was recorded daily until stabilization of germination. The data were submitted to analysis of variance; in the first experiment, the means were compared by Tukey test (P ≤ 0.05) and in the second study the regression analyzes were performed. The temperature of 20 °C showed the highest average of percentage and speed germination for E. precatoria seeds, both under lightness or darkness; the seeds were tolerant to desiccation

Euterpe precatoria Mart. é uma palmeira amplamente distribuída na bacia Amazônica. A semente é o único mecanismo de propagação desta palmeira, por ela não apresentar perfilhos. Vários fatores podem influenciar a germinação de sementes, como temperatura, luz e teor de água. O objetivo deste trabalho foi verificar a influência de diferentes temperaturas, regimes de luz e tolerância à dessecação na germinação de sementes de Euterpe precatoria Mart. No estudo de temperatura e luz, o delineamento experimental foi inteiramente casualizado em esquema fatorial 6 x 2 (seis temperaturas: 20 ºC, 25 ºC, 30 ºC, 35 ºC, 20-30 ºC e 25-35 ºC; na presença e ausência de luz), com quatro repetições e 25 sementes por parcela. No ensaio da tolerância à dessecação, o delineamento experimental foi o inteiramente casualizado; os tratamentos foram cinco teores de água nas sementes (27%, 20%, 13%, 12% e 11%) e quatro repetições, sendo cada parcela composta de 25 sementes. Anotou-se diariamente o número de sementes com emissão do botão germinativo até estabilização da germinação. Os dados obtidos foram analisados pela análise de variância; no primeiro experimento, as médias foram comparadas pelo teste de Tukey (P ≤ 0,05) e no segundo experimento, foi realizada análise de regressão. Para germinação de sementes de E. precatoria Mart., a temperatura de 20 °C foi a que apresentou maiores médias de porcentagem e velocidade de germinação tanto no claro como no escuro; as sementes mostraram-se tolerantes à dessecação
Keywords: Açai; Sementes; Germinação; Plantas - Efeito da luz; Água; Germination